A study of YouTube as an effective educational tool - Sharma, Dr Trishu; Sharma, Shruti (The journal of contemporary issues in business and government, 2021)
Social media has deeply penetrated into spaces of our lives. Our every little necessity is now just a click away which has made our lives comparatively much easier and convenient. Social media provides a new dimension to artists and learned people to share their art and knowledge. It covers update and knowledge of everything like health, politics, discovery, invention, science, mathematics and education. Since education is the sector which is largely influenced by social media tools, this research focuses on the how social media tools are harnessing education and learning process particularly ‘YouTube’. It is an inevitable fact that human brain processes images 60,000 times faster than text and the 90% of information transmitted to brain is visual. YouTube has proved to be an effective educational tool as it connects academicians, educators and researchers from all over the world and provide interesting, knowledgeable and engaging content which has added a new dimension to education by making it innovative as well as creative. The research method will be a study of focus groups divided in four categories i.e. elementary students, High school students, Graduation and academicians and educators.